PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS MASALAH BERBATUAN MULTIMEDIA DALAM PEMBELAJARAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP - Ratmiati, - (2019)
The current learning in schools is use to learning models that have generally been used from time to time or traditional ways. This requires innovation by utilizing existing technological developments. The purpose of this research is to explore the application of a model of learning based on problems and use multimedia in learning exposition text. The type of study is development research. The research design in this study was pretes-postest group design. The sample in this study was 8th-grade junior high school students amounting to 183 students. The result showed that the students' writing skill improved much better with the application of learning model based on problems aided by the presence of technology by multimedia in supporting the process of observing students in gathering material in writing exposition text. Based on the results of the pretest and postest, it was done showing an increase in the value of students in writing exposition text about environmental problems observed around them. With this study, learning, it can be concluded that students ability two write exposition text with the existence of problem-based on the learning model is at a level very good.